The effect of EFI to the carbureted single cylinder four stroke engine / Idris Ibrahim, Adibah Abdul Jalil and Shaharin A. Sulaiman - Ibrahim, Idris; Abdul Jalil, Adibah; A. Sulaiman, Shaharin (UiTM Press, 2010)
The study is conducted to study the EFI system performance as compared to the carburetted system for a single cylinder 4 stroke engine. In this study, a modelling and simulation study on the engine performance with EFI system was investigated utilizing engine simulation software, GT POWER software. The first part of the study is developing the carburetted engine model and simulating it using the GT POWER software. The results are validated using the result of engine dyno testing as well as the result of simulation using WAVE software. Then, the validated carburetted model is converted to EFI model, and simulated to investigate the performance of the engine installed with EFI system especially at low speed range. The findings conclude that the application of the EFI system to the carburetted single cylinder 4 stroke engine does produces improved performance in term of engine torque and power generated. The result of this study will provide platform for further research related to the investigation of the effect of EFI on the performance of 4 stroke single cylinder engine against environmental changes, the emissions output, life cycle analysis, engine wear and degradation over time, fuel injection study, engine control and tuning and etc.